Analysis the Application of Deming Model to Performance Management in the As-Sakinah Integrated Islamic Kindergarten - Reza Resmaliana; Andini Anggrainy; Putri Nur Atira; Satriadi Satriadi (Institut Teknologi dan Bisnis (ITB) Semarang, 2024)
Currently, many organizations are implementing the PDCA model to improve performance, one of which is As Sakinah TK in the city of Tanjungpinang. Even though the PDCA model has been implemented, there are still several obstacles in implementing the performance plan at As Sakinah TK. The aim of this research is to find out and describe the obstacles and how to apply the PDCA model to As Sakinah TK. This research method uses a qualitative descriptive method where the data collection technique is carried out by means of observation, interviews and documentation directly with the teacher and principal of As Sakinah Kindergarten. The results of this research are that As Sakinah TK has implemented the Deming/PDCA model, such as planning daily/weekly/monthly and even annual activities. Even though there are obstacles in its implementation, As Sakinah TK continues to implement daily and annual evaluations and take corrective actions to improve and improve performance.